2021
DOI: 10.3389/fnins.2021.749465
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Sensorimotor Function Through Neuromodulation After Spinal Cord Injury: Progress and Remaining Challenges

Abstract: Spinal cord injury (SCI) is a major disability that results in motor and sensory impairment and extensive complications for the affected individuals which not only affect the quality of life of the patients but also result in a heavy burden for their families and the health care system. Although there are few clinically effective treatments for SCI, research over the past few decades has resulted in several novel treatment strategies which are related to neuromodulation. Neuromodulation—the use of neuromodulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 154 publications
(187 reference statements)
0
11
0
2
Order By: Relevance
“…Maximum stimulation tolerance was shown by Manson et al to constitute approximately 56% of the intensity required to induce a motor response [40]. This sub-threshold intensity is within the range that clinical studies have reported functional improvements following cervical tSCS [2,36,37]. It is possible, however, that participants with relatively poor stimulation tolerances did not receive activation of posterior-root afferents.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Maximum stimulation tolerance was shown by Manson et al to constitute approximately 56% of the intensity required to induce a motor response [40]. This sub-threshold intensity is within the range that clinical studies have reported functional improvements following cervical tSCS [2,36,37]. It is possible, however, that participants with relatively poor stimulation tolerances did not receive activation of posterior-root afferents.…”
Section: Discussionmentioning
confidence: 81%
“…However, the variance may partially be attributable to current intensity, which was individualised for each participant based on their maximum tolerance. This choice of protocol was based on typical clinical procedures for determining current intensity [2,36,37]. The alpha and beta ERD/ERS of participants who received the highest intensity stimulation tended to be weaker compared to when tSCS was not present.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56] Reactivating paralyzed muscles involves restoring function in muscles that have been rendered immobile, usually due to nerve damage or injury that interrupts signaling from the brain to the muscle. [57] Delivering electrical stimulation to the motor nerves and muscles can reactivate them and produce functional movements. [58] The ability of neuromodulation to manage pain and spasticity can further facilitate the reactivation of paralyzed muscles.…”
Section: Neuromodulation Applicationsmentioning
confidence: 99%
“…Кроме фармакологических препаратов, для восстановления утраченных двигательных функций при спинальной травме с успехом применяются оптогенетическая модификация и периферическая электростимуляция, в том числе с синхрониза цией по электроэнцефалограмме (ЭЭГ) и машинным интерфейсом. Периферическая электростимуляция в арсенале методик нейро модуляции является наиболее доступным и безопасным методом реабилитации, используемым и в домашних условиях [19]. Альтернативу транскутанным воздействиям составляют инвазивные методики электрической нейро модуляции.…”
Section: электрическая стимуляция нейро модуляцииunclassified
“…В современной медицине электрическое воздействие на ткани и структуры относится к физиотерапевтическим вмешательствам, актуальность которых в век доказательной медицины подвергается критике. Ренессанс использования электростимуляции основан на положительных эффектах комплексной нейро модуляции у пациентов после травмы спинного мозга со стойкой утратой моторной и сенсорной функции [19] и доступности прикроватной визуализации нер вов с помощью ультразвука. Диагностические исследования нер вной проводимости возможны при транскутанном расположении активных электродов [12], но лечебное воздействие, особенно на миелинизированные нер вные волокна, возможно лишь при близком контакте с нер вом.…”
Section: электрическая стимуляция нейро модуляцииunclassified